A Survey: Services for Maladjusted School Children - Richard L. Simpson; Linda L. Edwards; Linda Ross (Educational Considerations, 1976)
There is strong evidence to support the contention that programs for meeting the needs of all behaviorally disordered and socially maladjusted school age children simply do not exist.